Was Duplessis Right? - Macdonald, Roderick (McGill Law Journal / Revue de droit de McGill, 2010)
Given the inclination of legal scholars to progressively displace the meaning of a judicial decision from its context toward abstract propositions, it is no surprise that at its fiftieth anniversary, Roncarelli v. Duplessis has come to be interpreted in Manichean terms. The complex currents of postwar society and politics in Quebec are reduced to a simple story of good and evil in which evil is incarnated in Duplessis’s “persecution” of Roncarelli.In this paper the author argues for a more nuanced interpretation of the case. He suggests that the thirteen opinions delivered at trial and on appeal reflect several debates about society, the state and law that are as important now as half a century ago. The personal socio-demography of the judges authoring these opinions may have predisposed them to decide one way or the other; however, the majority and dissenting opinions also diverged (even if unconsciously) in their philosophical leanings in relation to social theory (internormative pluralism), political theory (communitarianism), and legal theory (pragmatic instrumentalism). Today, these dimensions can be seen to provide support for each of the positions argued by Duplessis’s counsel in Roncarelli given the state of the law in 1946.